(NsOBRANIE SO^INENIJ W DWENADCATI TOMAH(B:s (NwOJNA I MIR(B: [(NrOMAN(B] (NtOM (B3 /s (N~ASTX (B5s - (NtOLSTOJ(B, (NlEW nIKOLAEWI^s ((NmOSKWA(B:s (NpRAWDA(B,s, 1984)
(Nw PQTYJ TOM sOBRANIQ SO^INENIJ WO[LO PRODOLVENIE ROMANA (B"(NwOJNA I MIR(B". s
rus
Keywords: (NrOMAN(B-(N\POPEQs; (NiSTORI^ESKIJ ROMANs